The Influence of Work Environment on Employee Performance Through Affective Commitment (A Research at PT X) - Nur Fadhilah, Amalia Rachmawati; Taufik, Edi Rahmat; Imron, Ali (Advances In Social Humanities Research, 2025)
The background of this research stems from the performance inequality challenges faced by PT X, where despite a significant increase in the number of employees from 131 in 2021 to 239 in 2023, employee performance distribution remains uneven, with 10 employees scoring the lowest performance rating in 2023, indicating potential work environment issues that need to be addressed. This research aims to analyze the influence of the work environment on employee performance with affective organizational commitment as a mediating variable in PT X. The background of this research is based on the inequality of employee performance as the number of workers increases from 2021 to 2023, despite an increase in performance values. This research uses a quantitative approach with the SmartPLS-based Structural Equation Modeling (SEM) method, involving 140 respondents from a total of 239 active employees. The results of the research show that the work environment has a positive and significant effect on employee performance and affective organizational commitment. Affective organizational commitment has also been shown to have a significant influence on employee performance and positively mediate the relationship between the work environment and performance. These findings indicate that effective management of the work environment, both from physical and psychosocial aspects, can be a key strategy in increasing employees' motivation, productivity, and long-term loyalty to the company.